Effect of Subshelf Melt Variability on Sea Level Rise Contribution From Thwaites Glacier, Antarctica. Issue 12 (4th December 2019) - Hoffman, Matthew J.; Asay‐Davis, Xylar; Price, Stephen F.; Fyke, Jeremy; Perego, Mauro
Abstract : Modeling and observations suggest that Thwaites Glacier, West Antarctica, has begun unstable retreat. Concurrently, oceanographic observations have revealed substantial multiyear variability in the temperature of the ocean water driving retreat through melting of the ice shelf that restrains inland glacier flow. Using an ensemble of 72 ice‐sheet model simulations that include an idealized representation of ocean temperature variability, we find that variable ice‐shelf melting causes delays in grounding line retreat, mass loss, and sea level contribution relative to steady forcing. Modeled delays are up to 43 years after 500 years of simulation, corresponding to a 10% reduction in glacier mass loss. Delays are primarily caused by asymmetric melt forcing in the presence of variability. For the "warm cavity" conditions beneath Thwaites Ice Shelf, increases in access of warm, deeper water are unable to raise water temperatures in the cavity by much, whereas increases in access of significantly colder, shallow water reduce cavity water temperatures substantially. This leads to lowered mean melt rates under variable ocean temperature forcing. Additionally, about one quarter of the mass loss delay is caused by a nonlinear ice dynamic response to varying ice‐shelf thinning rate, which is amplified during the initial phases of unstable, bed‐topography‐driven retreat. Mass loss rates under variability differ by up to 50% from ensemble mean values at any given time. Our results underscore the need for taking climate variability into account when modeling ice sheet evolution and for continued efforts toward the coupling of ice sheet models to ocean and climate models. Key Points: Including ocean temperature variability in a model of Thwaites Glacier leads to delayed mass loss Delay is mainly caused by the near‐isothermal nature of deep ocean water masses limiting melt increases Nonlinear ice dynamic response to ice shelf thickness change also contributes to mass loss delay Plain Language Summary: Warm ocean water melts the floating extensions of the Antarctic Ice Sheet called ice shelves. The thinning of the ice shelves reduces their ability to hold back the flow of the grounded glaciers behind them. This causes faster ice flow to the ocean and sea level rise. Recent ocean measurements around Antarctica have shown that the ocean temperature near West Antarctica varies by a few degrees over years or decades, which may be unrelated to climate change. However, modeling studies of how much Antarctic glaciers will contribute to sea level rise have largely ignored these short‐term fluctuations. We ran an ice sheet model of Thwaites Glacier, one of the largest glaciers in the region, that includes these short‐term fluctuations in ocean temperature dozens of times to investigate if they affect how quickly the glacier retreats. The model simulations that included the fluctuations always retreated more slowly than a run that ignored them. Depending on the strength and frequency of the fluctuations, the delay in glacier retreat and sea level rise was up to 10%. This delay occurs primarily because the ocean temperatures near Thwaites Glacier are already relatively warm for Antarctic conditions, and it is easier for temperature fluctuations to bring colder water to the ice shelf than it is to bring warmer water. Our results show that short‐term fluctuations due to climate variability can matter to glaciers in Antarctica and that ice sheet and climate models need to take them into account when projecting future sea level rise.